3D CNT/MXene microspheres for combined photothermal/photodynamic/chemo for cancer treatment - Gao, Wei; Zhang, Weihao; Yu, Haipeng; Xing, Wenge; Yang, Xueling; Zhang, Yongguang; Liang, Chunyong (Frontiers in Bioengineering and Biotechnology, 2022)
MXene nanosheets have shown exciting potential in nanomedicine because of their large surface area, intense near-infrared (NIR) absorbance, and good biocompatibility. However, their development in the direction of treating tumors is constrained by the limitations of existing design methodologies. These methodologies lack control over the size and distribution of tumors. Moreover, their photodynamic therapy (PDT) effect is poor. To address this unmet medical need, a simple strategy that processes Ti3C2 nanosheets with carbon nanotube (CNT) into a three-dimensional (3D) honeycomb structure having anti aggregation capacity was established. The structure can be used in disease phototherapy against tumors, bacteria, and viruses, such as photothermal therapy (PTT), photodynamic therapy (PDT), and multimodal synergistic therapy. In the present study, 3D CNT/MXene microspheres were obtained by the template method and spray-drying method. The microspheres possessed special photothermal effects and photothermal stability under NIR laser irradiation. Furthermore, the developed microspheres could achieve a maximum of 85.6% drug loading capability of doxorubicin (DOX). Under light irradiation at 650 and 808 nm, 3D CNT/MXene microspheres could efficiently produce singlet oxygen due to the effectiveness of CNTs as carries for TiO2 photosensitizers present on the MXene surface. Furthermore, in vitro studies had showed that 3D CNT/MXene-DOX effectively inhibited the proliferation of HeLa cells. Hence, this study provides a promising platform for future clinical applications to realize PTT/PDT/chemotherapy combination cancer treatment based on Ti3C2 nanosheets.